How Light Passes Through Ordered Macroporous Photonic Crystals Immersed in Solvents. (8th September 2020) - Lonergan, Alex; Hu, Changyu; O'Dwyer, Colm
Abstract : A better understanding of light transmission and relation to photonic bandgap in inverse opal photonic crystals is important when these structures are examined in liquids or solvents. We present a study of light tranmission through TiO2 and SnO2 inverse opals in several common solvents. The data and analysis identifies a correction to the Bragg-Snell theory and the photonic crystal unit cell definition that consolidates some inconsistencies between Bragg-Snell theory in various index solvents and physical measurements of inverse opals. We show experimental studies that suggest low fill factors in inverse opals are defined by porous material infilling all interstitial vacancies in the opal template to form an IO.